2011
DOI: 10.1152/ajpheart.00142.2011
|View full text |Cite
|
Sign up to set email alerts
|

PKCα mediates acetylcholine-induced activation of TRPV4-dependent calcium influx in endothelial cells

Abstract: Transient receptor potential vanilloid channel 4 (TRPV4) is a polymodally activated nonselective cationic channel implicated in the regulation of vasodilation and hypertension. We and others have recently shown that cyclic stretch and shear stress activate TRPV4-mediated calcium influx in endothelial cells (EC). In addition to the mechanical forces, acetylcholine (ACh) was shown to activate TRPV4-mediated calcium influx in endothelial cells, which is important for nitric oxide-dependent vasodilation. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 43 publications
3
88
3
Order By: Relevance
“…This is also consistent with old observations that the resting level of cGMP falls after removal of external Ca 2+ (White & Martin, 1989). In other studies, it has been shown that the TRPV4-mediated Ca 2+ signal was required for eNOS activation by ACh (Adapala et al, 2011;Zhang et al, 2009), also illustrating the necessity of Ca 2+ influx for endothelial NO release. Isshiki et al (Isshiki et al, 2004) suggested that agonist-stimulated eNOS activity in the endothelial cells was sensitive to external Ca 2+ -dependent acute changes in intracellular subcortical Ca 2+ signals and that basal eNOS activity was maintained and regulated by subplasmalemmal Ca 2+ equilibrated with extracellular Ca 2+ .…”
Section: Phenylephrine-induced Contractions and Nosupporting
confidence: 92%
“…This is also consistent with old observations that the resting level of cGMP falls after removal of external Ca 2+ (White & Martin, 1989). In other studies, it has been shown that the TRPV4-mediated Ca 2+ signal was required for eNOS activation by ACh (Adapala et al, 2011;Zhang et al, 2009), also illustrating the necessity of Ca 2+ influx for endothelial NO release. Isshiki et al (Isshiki et al, 2004) suggested that agonist-stimulated eNOS activity in the endothelial cells was sensitive to external Ca 2+ -dependent acute changes in intracellular subcortical Ca 2+ signals and that basal eNOS activity was maintained and regulated by subplasmalemmal Ca 2+ equilibrated with extracellular Ca 2+ .…”
Section: Phenylephrine-induced Contractions and Nosupporting
confidence: 92%
“…Effect of L-NAME. It has been previously reported that the TRPV4 agonist increases intracellular Ca 2ϩ concentration and activates endothelial NOS in endothelial cells (1,22). The role of NOS and NO in mediating or modulating cardiovascular responses to the TRPV4 agonist GSK1016790A were investigated in experiments with the NOS inhibitor L-NAME; these data are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TRPC3-and TRPC6-induced Ca 2+ inflow underpin the stimulatory effect of VEGF on endothelial proliferation, migration and permeability [18,231,236] , while ATP exploits TRPC3 to activate NF-κB and increase vascular cell adhesion molecule-1 expression [237] . TRPC3-driven NO synthesis and vasore- TRPV1 TRPV2 TRPV3 TRPV4 TRPV5 TRPV6 PCa/PNa and conductance (pS) [202] 10, 35-80 1-3, NM 12, 172 6, 90 > 100, 75 > 100, 40-70 Human coronary artery ECs [300] (+RT-PCR, WB, IHC) Human pulmonary artery ECs [415] +(RT-PCR) +(RT-PCR) +(RT-PCR) Human pulmonary microvascular ECs +(RT-PCR) Human cerebral microvascular ECs [272] +(RT-PCR, IC) Human cerebral arterioles ECs [305] +(RT-PCR, IHC) Human dermal microvascular ECs [319] +(RT-PCR, WB) Breast cancer derived microvascular ECs [319] +(RT-PCR, WB) Human umbilical vein ECs [227,277,296,301] +(RT-PCR) +(WB, IHC) Mouse aortic ECs [280,285,299,306] +(WB) +(RT-PCR, WB, NM, IHC) Mouse pulmonary artery ECs [313] +(WB, IHC) Mouse mesenteric artery ECs [27,280,302] +(RT-PCR, WB, IC) +(RT-PCR, IC) Mouse cerebral microvascular ECs +(RT-PCR) +(RT-PCR, WB) +(RT-PCR) Mouse dermal microvascular ECs [307] +(RT-PCR, WB) Mouse carotid artery ECs [290,296] +(IHC) Rat mesenteric artery ECs [226,275,302] +(WB) +(WB, IC, IHC) Rat femoral artery ECs [312] +(RT-PCR, IC) Rat pulmonary artery ECs [303] +(WB, IHC) Rat renal artery ECs [303] +(IHC) Rat cardiac microvascular ECs [303,…”
Section: A Drop In Luminal Camentioning
confidence: 99%
“…Under physiological conditions, TRPV4-mediated vasodilation, mainly via NO and EDHF production, is induced by both shear stress [27,290,291,296] and extracellular autacoids, such as Ach and UTP [297,301,305,306] . Although the cellular mechanisms linking membrane receptors to TRPV4 opening are still unclear, UTP utilizes PLA2 to gate the channel [297] , while PKCα mediates Ach-dependent activation [307] . Despite the evidence for TRPV4-evoked vasodilation, the baseline blood pressure is not affected in TRPV4 -/-mice [305,306] .…”
Section: Trpv2mentioning
confidence: 99%